Educação para a emancipação na era digital: um estudo sobre as Fanfics como recurso pedagógico para a aprendizagem de leitura crítica e de escrita criativa no ensino médio - Silva, Meirylane Lopes da (2019)
The education focused on the critical and autonomous thinking of the individual is the main instrument for the emancipation of subjects and for the transformation of society. Based at this theory, and in view of the educational possibilities emerged from the use of technological resources, this research was outlined. In this research, this theory is associated to the educational possibilities arising from the use of technological resources, especially the production and consumption of the digital genre fanfictions, in a multiliteracies perspective materialized through literary and digital literacy, in the construction of a pedagogical practice based on in the students' autonomy of thought and criticality through critical reading and creative writing. We had as general objective to analyze and prove the potential of the use of fanfics as a pedagogical resource for a practice of reading and writing critical and emancipatory. It is a qualitative bibliographic research, scientific support for the study of emancipation, multiliteracy and fanfictions, and participant. As epistemological approach, we define historical and dialectical materialism based on Triviños (2015) and Gamboa (2012), to apprehend education as an emancipatory phenomenon amidst the economic-political determinants that today shape school education as an uncritical transmission space of accumulated knowledge. Through open questionnaires and participant research — development of a pedagogical proposal with the use of fanfictions in a public school in João Pessoa / PB —, we obtained the necessary information for object analysis. Data analysis, based on dialectical hermeneutics with theoretical foundation in Minayo (2002; 2009; 2010), revealed three empirical categories: appropriation, authorship and autonomy of thought. The research makes it possible to state that the pedagogical use of fanfictions provides a space for interaction, creativity and autonomy of thought to the students, enabling them to develop, through the synergistic relationship between school and technology, real experiences of productive and collective use of the language that corroborate for their emancipation.